Enzyme Biocatalysis for Sustainability Applications in Reactors: A Systematic Review - Chook, Kay Yi *; Aroua, Mohamed Kheireddine *; Gew, Lai Ti * (American Chemical Society, 2023)
Enzyme biocatalysis is well known for its biodegradability and environmentally friendly conditions. Its novel properties such as high reaction selectivity and mild reaction conditions prove that it is a promising alternative that can overcome the global resource scarcity of the conventional chemical catalysts that are of a nonrenewable source. In this study, we documented the advancements and breakthroughs in emerging biocatalysis reactor technologies spanning over a decade. We aim to encapsulate the remarkable progress and innovations witnessed within this dynamic field. Thus, we reviewed 48 articles related to enzyme biocatalysis in the production of glycerides using reactors. The reaction parameters using a biocatalysis route were reviewed systematically and discussed in our study. In the biocatalysis transformation, the processes mainly focus on the conversion of raw material into product. In the optimization of biocatalysis, temperature and residence time parameters have been thoroughly researched in order to maximize the productivity of the enzyme activity. In the selection of reactors, the type of reactor and its agitator play a vital role in enzyme activity. We anticipate that the greenness of biocatalysis transformation could be improved if the enzymes in waste streams could be converted from another reaction to functional products. This work may serve as a stepping stone for the biocatalysis industry, acting as a precursor for industries or individuals interested in exploring this evergreen field.